USA Country Studies - Zsolnay, Lilo. (Lutsk Media, 1998)
This book is recommended for the students of general secondary specialized schools, gymnasiums, lyceums, and English language departments. The materials are compiled and adapted from original American texts using American English.
Keywords: Country Studies